SC12 Props – enhancing character development using performing arts pedagogy. (17th November 2016) - Gibson, J; Greene, L; Gough, S
Abstract : Background: Simulated Patients (SP) are trained to portray different roles in healthcare education (Nestel and Bearman, 2015). This project developed and evaluated the 'Train-The-Simulated Patient' (2TSP) package (Greene and Gough, 2015). The 2TSP package provides a standardised approach to training SPs, featuring an e-learning course and face-to-face workshop. The innovative 2TSP package includes The PrOPS Process© (Gibson, 2015), which blends performing arts pedagogies to enhance characterisation and role portrayal for non-arts professionals. Utilising Process Drama techniques, The PrOPS Process© involves four-stages of SP development: Profile building, Objective-setting, Physicality and Speech modification. Methodology/methods: A pragmatic, mixed-methods design facilitated a comprehensive exploration of the 2TSP package; University ethical approval was obtained. None of the participants (NHS Service Users/volunteers, NHS staff, university staff and students, n = 34) had completed SP training previously. Data collection methods included an electronic evaluation questionnaire featuring open and closed questions. Results: All participants commented that they would recommend the 2TSP workshop to others. The PrOPS Process© evaluated positively, with participants: Valuing performing arts techniques to enable a greater understanding of the character they were developing Able to connect with the perspectives and feelings that patients may experience during scenarios Reporting improved levels of confidence in assuming future SP roles Conclusions: The 2TSP package is implemented throughout the region with performing arts methodology embedded throughout. The PrOPS Process© aims to support users through character development, particularly in non-arts settings. It is anticipated that this will enhance role portrayal skills and improve the learning environment and thus, the quality of learning. References: Gibson J. Train The Simulated Patient. Manchester: Manchester Metropolitan University; 2015. http://www.cheshire.mmu.ac.uk/dca/projects/train-the-simulated-patient/ Greene L, Gough S. Simulated Patients: blending performing arts pedagogy and healthcare education. Final Project Report. Manchester: Health Education North West; 2015. Nestel D, Bearman M. Chapter 1: Introduction to simulated patient methodology. In: Nestel D, Bearman M, eds. Simulated Patient Methodology: Theory, Evidence and Practice . West Sussex: Wiley Blackwell; 2015:1–4.